Improvement of Surface-Enhanced Raman Scattering Method for Single Bacterial Cell Analysis - Yan, Yingchun; Nie, Yong; An, Liyun; Tang, Yue-Qin; Xu, Zimu; Wu, Xiao-Lei (Frontiers in Bioengineering and Biotechnology, 2020)
Surface-enhanced Raman scattering (SERS) is a useful tool for label-free analysis of bacteria at the single cell level. However, low reproducibility limits the use of SERS. In this study, for the sake of sensitive and reproducible Raman spectra, we optimized the methods for preparing silver nanoparticles (AgNPs) and depositing AgNPs onto a cell surface. We found that fast dropwise addition of AgNO3 into the reductant produced smaller and more stable AgNPs. Compared with that observed after simply mixing the bacterial cells with AgNPs, the SERS signal was significantly improved after centrifugation. To optimize the SERS enhancement method, the centrifugal speed, method for preparing AgNPs, concentration of AgNPs, ionic strength of the solution used to suspend the cells, and density of the cells were chosen as impact factors and optimized through orthogonal experiments. Finally, the improved method could generate sensitive and reproducible SERS spectra from single E. coli cells, and the SERS signals primarily arose from the cell envelope. We further verified that this optimal method was feasible for the detection of the incorporation of isotopes by the cells and the discrimination of different bacterial species. Our work provides an improved method for generating sensitive and reproducible SERS spectra.